1987
DOI: 10.1111/j.1365-2389.1987.tb02142.x
|View full text |Cite
|
Sign up to set email alerts
|

The fate at several time intervals of 15N‐labelled ammonium nitrate applied to an established grass sward

Abstract: SUMMARY 15N‐labelled ammonium nitrate solution was applied in late April to circular, enclosed micro‐plots prepared by pressing open‐ended polypropylene cylinders into an established sward of perennial ryegrass. Cylinders were removed from the ground at intervals between 2 and 370 days after the application and assessments made of the distribution of 15N in plant and soil components. Of the added labelled N, 54.7% was recovered in the herbage which was cut four times during the growing season and again at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
2
2

Year Published

1989
1989
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(40 citation statements)
references
References 18 publications
3
33
2
2
Order By: Relevance
“…This is shown by Bristow et al (1987) NO3, where the proportion of total N uptake in the harvested plant varied from 2 % on the day of application to 16.8% after 27 days.…”
Section: Incubation Time (Assumption 3)mentioning
confidence: 93%
“…This is shown by Bristow et al (1987) NO3, where the proportion of total N uptake in the harvested plant varied from 2 % on the day of application to 16.8% after 27 days.…”
Section: Incubation Time (Assumption 3)mentioning
confidence: 93%
“…This suggests that N was stored in the soil in a form not measured as soil extractable inorganic N and/or plant material remaining in the plot. Tracer studies have shown that considerable fertilizer N can be incorporated into organic fractions in the soil (Bristow et al 1987;Ledgard et al 1988;Malhi 1995;Stevens et al 1986), and that the sizes of these fractions increase with time. Whitehead et al (1990) estimated N released by mineralization in the first year after cultivation increased from 70 kg N ha -1 in a 1-yr-old stand to 300 kg N ha -1 in a 15-yr-old stand.…”
Section: Discussionmentioning
confidence: 99%
“…This may explain why clover content may become low, but few accounts proceed to explain how co-existence is achieved; that is, how a range of mixtures of low clover content are nonetheless sustained. Studies of the dynamics and the cyc1ing and fate of N from urine patches (temporally and spatially heterogeneous environments) have been made (see Ryden, 1984;Bristow, Ryden and Whitehead, 1987;Marriott, Smith and Baird, 1987), and these c1early re1ate to the perturbation and alternation of species advantage explored here. However, the model predicts co-existence even with constant N inputs.…”
Section: Dynamic Solutions With a Soil Organic Matter Delaymentioning
confidence: 99%